2020
DOI: 10.1055/s-0040-1712831
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Study of Proximal Femur Geometry and Its Clinical Application

Abstract: The implants for fixation of proximal femur fractures and joint replacements have been designed taking into consideration of the anthropometry of the western population which vary from other ethnic groups. The present study aimed to study the morphology of the upper end of femur in relation to its various diameters and angles and compare the external and internal geometry of proximal femur as obtained from radiographs, with actual measurements on cadaveric specimens in Indian population. Seventy five pairs (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 10 publications
(15 reference statements)
4
47
2
Order By: Relevance
“…al. (14) in an anthropometric study demonstrated that the average FHD in European population to be 43.53±3. 4 The age of 40-80 years were chosen in this study since it had been demonstrated to be the most frequent age vulnerable to proximal femoral surgery (18).…”
Section: Radiological Evaluation Of the Proximal Femoral Geometric Fementioning
confidence: 98%
See 1 more Smart Citation
“…al. (14) in an anthropometric study demonstrated that the average FHD in European population to be 43.53±3. 4 The age of 40-80 years were chosen in this study since it had been demonstrated to be the most frequent age vulnerable to proximal femoral surgery (18).…”
Section: Radiological Evaluation Of the Proximal Femoral Geometric Fementioning
confidence: 98%
“…Many studies had focused on the head diameter for different ethnic populations (8,14). Siwach RC et.…”
Section: Radiological Evaluation Of the Proximal Femoral Geometric Fementioning
confidence: 99%
“…In the first step digital roentgenograms (AP view) of all the bones selected for the study were taken using standardized techniques [2]. The bones were placed directly over the X-ray cassette to minimize the magnification.…”
Section: A-femoral Head Offset B-superior Inferior Diameter Of Head Cmentioning
confidence: 99%
“…In case of THR, it is mandatory that the design and dimensions of the femoral component, match (best-fit) the anatomy of the femur more so in cement-less variety. Significant variations are noted in the proximal femoral geometry of different races and ethnic groups [2][3][4][5]. Studies show that genetic and environmental factors including lifestyle determine the geometry of the proximal femur [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation